Optimization of Potassium Supply under Osmotic Stress Mitigates Oxidative Damage in Barley - Tavakol, Ershad; Jákli, Bálint; Cakmak, Ismail; Dittert, Klaus; Senbayram, Mehmet (Plants (Basel), 2021)
Potassium (K) is the most abundant cation in plants, playing an important role in osmoregulation. Little is known about the effect of genotypic variation in the tolerance to osmotic stress under different K treatments in barley. In this study, we measured the interactive effects of osmotic stress and K supply on growth and stress responses of two barley cultivars (Hordeum vulgare L.) and monitored reactive oxygen species (ROS) along with enzymatic antioxidant activity and their respective gene expression level. The selected cultivars (cv. Milford and cv. Sahin-91Sahin-91) were exposed to osmotic stress (−0.7 MPa) induced by polyethylene glycol 6000 (PEG) under low (0.04 mM) and adequate (0.8 mM) K levels in the nutrient solution. Leaf samples were collected and analyzed for levels of K, ROS, kinetic activity of antioxidants enzymes and expression levels of respective genes during the stress period. The results showed that optimal K supply under osmotic stress significantly decreases ROS production and adjusts antioxidant activity, leading to the reduction of oxidative stress in the studied plants. The cultivar Milford had a lower ROS level and a better tolerance to stress compared to the cultivar Sahin-91. We conclude that optimized K supply is of great importance in mitigating ROS-related damage induced by osmotic stress, specifically in drought-sensitive barley cultivars.